Ghana : 2009 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Supplement; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Ghana. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2009 Article IV Consultation highlights that Ghana's overall financial system remains stable. The regulatory and supervisory framework is strong, backed by a modern payment and settlement infrastructure. Financial soundness indicators point to a banking system that is liquid and with capital above statutory levels. Directors have supported the authorities' efforts to restore macroeconomic stability by seeking to achieve fiscal sustainability. Noting that Ghana remains at moderate risk of debt distress, Directors have emphasized that further fiscal consolidation will be critical over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet